The interplay between cholesterol (and other metabolic conditions) and immune-checkpoint immunotherapy: shifting the concept from the "inflamed tumor" to the "inflamed patient" - Melissa Bersanelli; Alessio Cortellini; Sebastiano Buti (Taylor & Francis Group, 2021)
The predictive ability of metabolic conditions, such as hypercholesterolemia, on the outcome of cancer patients to immune-checkpoint inhibitors (ICIs) therapy, has been recently explored. The reasons for their value in this setting are to be searched in the individual himself more than in his tumor, as the target of the immune-checkpoint blockade is the immune system. The efficacy of ICIs on the tumor may be based on two simple premises: 1) the physiological immune function has been blocked, and 2) the tumor progression (mainly) depends on this block. The metabolic syndrome may represent the epiphenomenon of an "inflamed patient," no longer able of physiological functions required to prevent chronic inflammatory events. The metabolic dysfunction could represent merely "a biomarker" of the patient who satisfies both the two premises reported above. Suggestions from preclinical and translational researches should be transferred in the clinical setting, implementing randomized clinical trials with observational endpoints such as the effect of concomitant drug medications and the impact of blood cholesterol levels and other metabolic conditions on the outcome of ICI treatment.